2017
DOI: 10.3892/ol.2017.6536
|View full text |Cite
|
Sign up to set email alerts
|

Membranous type matrix metalloproteinase 16 induces human prostate cancer metastasis

Abstract: Abstract. Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes, which perform a crucial role in the metastatic spread of cancer. MMP2 and MMP9 are important cancer-associated MMPs in the invasion and metastasis of the majority of carcinomas. As a new member of the membrane-type MMPs, the function of MMP16 associated with invasion and metastasis of cancer remains unclear. In the present study, MMP16 expression in prostate cancer (PCa) tissues and cells was examined, and the high expression of MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…MMPs are a family of proteolytic enzymes that play a crucial role in cancer metastasis by degrading the extracellular matrix, along with a variety of cell surface receptors and signaling molecules (44). Jiang et al reported that high expression of MMP16 is associated with advanced prostate tumor stage and PCa metastasis (45). Knockdown of MMP16 in PC3 cells led to decreased migratory and invasive properties of PC3 cells (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are a family of proteolytic enzymes that play a crucial role in cancer metastasis by degrading the extracellular matrix, along with a variety of cell surface receptors and signaling molecules (44). Jiang et al reported that high expression of MMP16 is associated with advanced prostate tumor stage and PCa metastasis (45). Knockdown of MMP16 in PC3 cells led to decreased migratory and invasive properties of PC3 cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported that high expression of MMP16 is associated with advanced prostate tumor stage and PCa metastasis (45). Knockdown of MMP16 in PC3 cells led to decreased migratory and invasive properties of PC3 cells (45). ROCK1 is an effector kinase of the small GTPase RhoA (46).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the PMD-associated DMS, we also identified DMS with focal changes in methylation in gene promoter regions. The gene of matrix metalloproteinase 16 (MMP16), a proteolytic enzyme involved in the development of PCa progression and metastases [23], is located in a frequent PMD. However, we identified cg12818557 located in the promoter region of MMP16 as a strong predictor, with almost 20% methylation gain in the poor compared to the good prognosis group.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, our data indicate that Wnt3A treatment of DCIS cells resulted in increased MMP16 mRNA levels. The effect of MMP16 on cancer progression has been reported in multiple cancers, such as prostate cancer, colon cancer and melanoma, where it promotes migration, invasion, and metastasis 53,54 . Higher levels of MMP16 are detected in cancer tissues compared to normal tissues and they are also associated with poor prognosis 53 .…”
Section: Discussionmentioning
confidence: 99%